Demographic associations for autoantibodies in disease-free individuals of a European population - Haller-Kikkatalo, Kadri; Alnek, Kristi; Metspalu, Andres; Mihailov, Evelin; Metsküla, Kaja; Kisand, Kalle; Pisarev, Heti; Salumets, Andres; Uibo, Raivo (Scientific reports, 2017)
The presence of autoantibodies usually precedes autoimmune disease, but is sometimes considered an incidental finding with no clinical relevance. The prevalence of immune-mediated diseases was studied in a group of individuals from the Estonian Genome Project (n = 51,862), and 6 clinically significant autoantibodies were detected in a subgroup of 994 (auto)immune-mediated disease-free individuals. The overall prevalence of individuals with immune-mediated diseases in the primary cohort was 30.1%. Similarly, 23.6% of the participants in the disease-free subgroup were seropositive for at least one autoantibody. Several phenotypic parameters were associated with autoantibodies. The results suggest that (i) immune-mediated diseases are diagnosed in nearly one-third of a random European population, (ii) 6 common autoantibodies are detectable in almost one-third of individuals without diagnosed autoimmune diseases, (iii) tissue non-specific autoantibodies, especially at high levels, may reflect preclinical disease in symptom-free individuals, and (iv) the incidental positivity of anti-TPO in men with positive familial anamnesis of maternal autoimmune disease deserves further medical attention. These results encourage physicians to evaluate autoantibodies in addition to treating a variety of patient health complaints to detect autoimmune-mediated disease early.